Distribution and stocks of mass bottom and demersal fishes by areas of the northwestern Japan Sea - Pavel V. Kalchugin; Sergei F. Solomatov; Maksim I. Boyko (Известия ТИНРО)
Features of seasonal distribution are considered for the most abundant fish species in the northwestern Japan Sea and their stocks are assessed on the data of the bottom trawl survey over the shelf and continental slope from Peter the Great Bay to the Soya (La Perouse) Strait conducted by Pacific Fisheries Research Center (TINRO) on April 1 - July 8, 2015. The total biomass of bottom and demersal fish species in the surveyed area is estimated as 584.5 · 103 t, including 137.8 · 103 t of flatfishes (23.5 %) and 135.3 · 103 t of sculpins (23.1 %). Deep-water sealyeye plaice had the maximal biomass among flatfishes with the stock of 63.8 · 103 t, it concentrated mainly at southern Primorye (28.3 · 103 t). Its stock was comparable with the total flatfish biomass at western Sakhalin (61.2 · 103 t). The family Cottidae was also very important in bottom communities of the northwestern Japan Sea, but this group had higher species diversity: 22 species. Blackedged sculpin, graypurple sculpin, plain sculpin, and great sculpin were the most abundant sculpins and dominated in this group in different proportion in all areas. The total stock of these four species was 110.6 · 103 t (81.7 % of the total biomass of Cottidae), including 25.8 · 103 t in Peter the Great Bay, 45.7 · 103 t at southern Primorye, and 20.4 · 103 t at western Sakhalin. The sculpins dwelled mostly shallower than 400 m, only 3 % of their biomass was assessed deeper. The observed values of the stocks were close to their mean values, with exception of Peter the Great Bay, where the assessed stocks were considerably lower of the mean values. The underestimation was supposedly caused by early timing of the survey start that wasn’t optimal taking into account seasonal migrations of some mass species. For example, the main concentrations of flatfishes were located in early April deeper than the survey limit.